Estimação em tempo real de potência e impedância da rede elétrica utilizando a Transformada Wavelet Packet Estacionária - Alves, Dênis Keuton (2019)
This thesis proposes the application of the stationary discrete wavelet packet transform (SDWPT) to properly estimate primary power quantities (active, total apparent, nonactive power, and power factor), and distortion power. Additionally, the analysis tools of signal processing developed in this work allowed the development of a method for estimating the grid impedance. The SDWPT provides a uniform frequency band and possesses the timeinvariance property, which is ideal for power estimation and grid impedance estimation in the real-time. The method of estimation of power quality indices was assessed and compared to the IEEE Standard 1459-2010 under different operational scenarios, where stationary synthetic waveforms and with both stationary and nonstationary power quality disturbances were emulating in an experimental setup. Regarding the grid impedance estimation, the current study was developed to identify the impedance of low voltage electric grids interconnected with distributed power generation systems. The validation of the proposed method was accomplished in a distributed generation implemented through the photovoltaic plant of 8 kWp connected to the point of common coupling of a threephase feeder composed by a transformer of 15 kVA.